The Case of Learning by Doing and its Applications in Tanzania - Nungu, Amos (My University, 2013)
The Communication System Design (CSD) Course offered at the Royal Institute of Technology (KTH) in Sweden is a problem oriented, project-driven environment integrating development and learning. It is a framework for learning by solving real world problems involving Mastervstudents from various fields of specialization, mentored and supervised by their teachers and industrial experts. CSD is based on integration of Research, Education and Innovation, Problem-oriented, projectdriven learning, peer learning and vicarious learning where diverse teams of students work in relay projects with handover procedures. The paper presents a case study on project based model of learning (learning by doing) that was used to implement a very big local area network Bunda and Serengeti Districts in Tanzania. The actual implementation involved teams of students from KTH working together with local employees.
Keywords: SOCIAL SCIENCES::Social sciences::Education; Innovation; Problem-oriented; Project-driven learning; peer learning; vicarious learning